A hybrid hydrogel system composed of CdTe quantum dots and photonic crystals for optical anti-counterfeiting and information encoding–decoding. Issue 10 (21st February 2022) - Pan, Guoyi; Yan, Jingye; Tang, Zilun; Zhang, Jieheng; Lin, Xiaofeng; Yang, Dongpeng; Wu, Jianyu; Lin, Wenjing; Yi, Guobin
Abstract : A novel hybrid hydrogel system composed of CdTe QDs and SiO2 PCs was developed for optical anti-counterfeiting and information encoding–decoding. Abstract : The composite materials combining quantum dots (QDs) and photonic crystals (PCs) could produce complex and high-dimensional anti-counterfeiting patterns, which solves the problems of simple coding information and a low anti-counterfeiting level of monochromatic materials. Herein, we reported a novel hybrid hydrogel made up of CdTe QDs and SiO2 PCs for optical anti-counterfeiting and information encryption–decryption. The hybrid hydrogel was prepared by adding CdTe QDs and gelatin-methacryloyl (GelMA) precursor filler into a poly(ethyleneglycol) diacrylate (PEGDA)-based inverse opal hydrogel. Firstly, GelMA-based pregel and CdTe QDs were photo-cured to obtain patterned fluorescent labels, whose fluorescence intensities were greater than those of the single CdTe QD solution. Then, the PEGDA-based inverse opal hydrogel and hybrid hydrogel containing CdTe QDs and SiO2 PCs were prepared, both of which had angular dependence of structural colors and good water wettability. The hybrid hydrogel had a double optical anti-counterfeiting function because it also had fluorescence characteristics under UV light. Moreover, through a simple combination of CdTe QDs and PCs, more complex and higher-dimensional optical composite coding effects were achieved, providing a good single platform for exploring the combination effects. In addition, the preparation process was simple and flexible, which only need to provide visually confused structural and fluorescence color, such as our patterned "100". Then, the hidden signal could be quickly identified by relevant spectral detection. Therefore, this work offers a simple avenue for encoding complex information from a single hybrid hydrogel platform and provides a method for rapid information decoding.